Game-Based Learning in Biology Education: Designing and Evaluating the BioQuest Mobile Learning Prototype - Meirizka Putri, Nadya; Hikmawan, Rizki (Jurnal Paedagogy, 2026)
Abstract: This study aims to develop and evaluate BioQuest, a mobile educational game prototype for junior high school Biology learning in Indonesia, using a User-Centered Design (UCD) approach. The evaluation was conducted through two iterative cycles focusing on interface design, usability, cognitive load profiles, and the relationship between usability and extraneous cognitive load (ECL). Data were collected using several instruments, including Cognitive Walkthrough (CW), the System Usability Scale (SUS) adapted from task performance on the Maze platform, the User Experience Questionnaire Plus (UEQ+) covering 10 dimensions, a cognitive load questionnaire measuring intrinsic cognitive load (ICL), extraneous cognitive load (ECL), and germane cognitive load (GCL), as well as semi-structured interviews. The first evaluation cycle (UE1) involved 13 participants, while the second cycle (UE2) involved 21 participants, including both returning and newly recruited students. The results showed that UE1 achieved a SUS score of 86, while UE2 achieved a score of 82.5; both scores were categorized as “very good” and exceeded the average usability threshold. All 10 UEQ+ dimensions in both cycles were classified within the very positive category (2.00–2.73 in UE1 and 2.18–2.60 in UE2). The cognitive load profile was optimal across both evaluation cycles, with extraneous cognitive load (ECL) remaining controlled (low in UE1 and moderate in UE2) and germane cognitive load (GCL) consistently high (M = 5.74 in UE1; M = 6.19 in UE2), indicating strong cognitive engagement during learning activities. A descriptive comparative analysis revealed a negative relationship between usability and ECL across iterations. These findings provide empirical evidence that a UCD-based iterative approach can effectively support the development of mobile educational games with high usability, positive user experience, and a cognitive load profile that promotes meaningful Biology learning at the junior high school level.